Individual monitoring of the countermovement rebound jump in Division I female basketball players across a competitive season: Using the model statistic and coefficient of variation approach - Ghigiarelli, J. J.; Saldutti, D. V.; Pottorf, O. A.; Sell, K. M.; Gonzalez, A. M. (The Journal of Strength and Conditioning Research, 2025)
This study monitored neuromuscular fatigue using the countermovement rebound jump (CMRJ) test in 13 Division I female basketball players during a competitive season. The players were tested twice a week by performing 3 sets of 2 jumps on a force plate. Thirteen CMRJ metrics were analyzed across 20 sessions. A combined model statistic and coefficient of variation analysis enabled the use of a single-subject repeated-measures design to detect individual player decrements (fatigue) between testing days and baseline measures. Two-way repeated-measures analysis of covariance between high- and low-minute players was used to analyze CMRJ metrics. Except for a simple main effect of the modified reactive strength index for high-minute players, no other significant main effects were reported for the group, time, or interaction for the remaining CMRJ metrics. The analysis yielded 819 individual fatigues, with the highest percentages of fatigue for the countermovement jump (CMJ) jump height (JH) (12.3%) and CMJ average braking power (12.3%). For the rebound jump, JH exhibited the highest percentage of fatigue (9.9%). Although the results of the team analysis were not significantly different, a select few players contributed to a higher percentage of fatigue, justifying the importance of inspecting the data by individuals in addition to team averages.